Ecological consequences of human depopulation of rural areas on wildlife: A unifying perspective. (December 2020) - Martínez-Abraín, Alejandro; Jiménez, Juan; Jiménez, Ignacio; Ferrer, Xavier; Llaneza, Luis; Ferrer, Miguel; Palomero, Guillermo; Ballesteros, Fernando; Galán, Pedro; Oro, Daniel
Abstract: The depopulation of rural areas by humans (or rural exodus) in southern Europe, and the associated abandonment of cropland, had marked ecological consequences on wildlife, which became evident approximately fifteen years ago. Shrub and tree encroachment, and the expansion of forest birds and the formerly persecuted mammalian ungulates and carnivores, were highlighted as the major consequences of the rural exodus in Italy. In this report, we provide a more integrative view, and show that a rural exodus also explains other ecological phenomena that are usually treated independently. After reviewing the ecological consequences of the rural exodus that has been affecting a large part of Spain during the last six decades, we suggest that this set of ecological consequences also includes the movement of shy-selected predators and large, big game species out of their former ecological refuges, as well as increased frequencies of individuals with bolder-behaviours in recovering populations. We develop a tentative conceptual model linking the increasing approach of wildlife to anthropogenic habitats and human depopulation of rural areas. These links are created by the increasing difficulty to survive and reproduce in recovering, high-predation wild areas, due to mesopredator release and the loss of fear to humans, among other factors. We acknowledge that the recovery of formerly persecuted wildlife in depopulated landscapes has been helped by conservation policies, but we suggest that policies alone cannot explain the observed changes. Finally, we propose that the processes we analyse on a national scale could be taking place in Europe on a continental scale as well, and will most likely occur in the future in other regions of the world, with the current growth in economies. Highlights: The ecological consequences of the human depopulation of rural areas in Southern Europe are revisited. We suggest a new unifying view of the set of consequences including some processes that are commonly analysed as separate phenomena. We develop a conceptual model linking the abandonment of former ecological refuges to the increasing approach of wildlife to urbanised areas. The process analysed at a national scale could be operating at a continental scale and it will likely happen in many currently growing economies.